Co-Learn: collaborative learning - Center for International Forestry Research (Center for International Forestry Research, 2003)
Co-learn is a computer software package that facilitates and enables users to navigate around a range of tools and processes. It is intended to be a meta-tool, implemented as a software interface and navigation aid for a suite of computer-based learning support tools. It seeks to support adaptive and collaborative management (ACM) of natural resources by helping people to enjoy learning processes in groups. This tool uses the metaphor of a map with a bus routes that present to the users several options and aids to getting from any point in an abstract management landscape to another, by a route that users select themselves. Because Co-Learn is a map on a computer, users can make the map interactive allowing them to access resources-information (e.g. manuals, guides, anecdotes/experiences, etc.) and tools (software such as Co-view, CIMAT, SSI, analytical packages etc.) - that would make their journey easier and more likely to be successful. Co-Learn is intended to be used by both participants in group learning processes, as a navigation aid, and by facilitators of such processes for planning, technical support and record keeping. The present version is a full-fledged 'proof of concept' demonstrator released explicitly for evaluation.